Leading out loud : a guide for engaging others in creating the future - Pearce, Terry, 1941- (Recorded Books, 2013)
Much has changed in the world since the original publication of Leading Out Loud, Terry Pearce's book on authentic leadership communication. Now, more than ever, the development of a leader's message is as crucial to success as the delivery of that message. In the third edition of his classic book, Terry Pearce shows leaders in all sectors how to communicate their values and vision to inspire commitment. In this important resource, Pearce continues to broaden the application of core principles, putting the spotlight on every day, spontaneous communication. New examples, covering the range of today's multi-faceted communication, show the application of the sage advice Pearce offers. Readers will see how to develop a Personal Leadership Communication Guide that supports any venue, through any media and in multiple cultures. This completely revised and updated version of the bestselling classic is designed to meet the communication needs of today's leaders.